Tobin tax effects seen from the foreign exchange market's microstructure - Alexander Mende; Lukas Menkhoff (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2003)
The Tobin tax is in high demand for many groups. Despite its popularity, research has not yet made full use of available insights from the recent microstructure literature. The role of banks in foreign exchange trading is quite different from what proponents usually assume. The most probable decisive group for shorter-term exchange rate movements is asset managers. They speculate under comparatively longer horizons than FX dealers although they also tend to behave short-termist. There is no tax rate that could influence their behavior and at the same time keep the desired high liquidity. Thus no uniform proportional Tobin tax can reach its goals.
Keywords: F31; 330; Tobin tax; market microstructure; Tobinsteuer; Devisenmarkt; Mikrostrukturanalyse; Devisenspekulation; Theorie